Symptomatic Tarlov Cyst – Case Report and Review of the Literature (Bangladesh Journal of Neurosurgery, 2024)
Here we describe the case of a 53 year old woman presenting with low back pain with  radiation was diagnosed with sacral bilateral Tarlov cyst. She was treated by  laminectomy, disintegration of cyst and duroplasty. Histopathological examination of  the cyst wall was confirmed the diagnosis. Symptomatic Tarlov cysts are extremely  rare, commonly presenting as sacral or lumbar pain syndromes, sciatica or rarely as  cauda equina syndrome. Tarlov cysts should be considered in the differential  diagnosis of patients presenting with these complaints. Bang. J Neurosurgery 2023; 12(2):125-128